IMPLEMENTATION OF RADIO URBANRKM 99.5 FM REBRANDING TO CREATE COMPANY’S NEW IMAGE - Karina Putri Palasari Triyana; Aan Setiadarma (Avant Garde, 2016)
Background of research is there is a rebranding of URBANrkm 99.5 FM become Smooth Radio who have very different characteristics that caused by changing ownership. Rebranding makes the company should face all of external stakeholder’s respons and doing all steps implementations of any changes to create the company’s new image. The theory used is communication, public relations, implementation, rebranding and the concept definitions of image. Research Methode used is qualitative approuch with descriptive as the type of research. Key informan of this research is the Director Program of URBANrkm 99.5 FM Radio and Smooth Radio, with three informants, marketing communications of Smooth Radio, and two loyal listener of URBANrkm 99.5 FM Radio. Research Result, in making program and public relation’s activities on rebranding phase, Smooth Radio use five steps of implementation that appropriate with Wheelen and Hunger’s theory, there are also some change that done by Smooth Radio to create their new image. Conclusion, URBANrkm 99.5 FM Radio succesed to maintain their image on external stakeholder’s eyes when their crisis time through their public relation’s activities that they done. In another hand, Smooth Radio also succesed to show their image through all implementation’s step they done and by changing their identity with some evaluation that should to be their attention.